Hydrochemical parameters in a portion of the paraíba do sul river hydrographic basin, são josé dos campos city, são paulo state, brazil - Lee, Isabella G. [UNESP]; Bonotto, Daniel M. [UNESP] (WITPRESS LTD., 2020)
This paper describes a hydrochemical study held in a portion of the Paraíba do Sul river hydrographic basin that is located in São José dos Campos city at eastern of São Paulo State, Brazil. It comprises Lambari river, a tributary of the Paraíba do Sul river, which crosses the installations of the Henrique Lage Oil Refinery (REVAP). Here is reported the hydrochemical parameters of the Lambari river waters that drain the refinery in order to identify possible impacts on the water resources due to the presence of the refinery. All samples analyzed (32) exhibited a similar hydrochemical pattern, except sample IL-02, which presented different values for most of the parameters analyzed. The samples exhibited pH values between 6.16 and 7.41 and Eh values between +260 and +324 mV, except for one outlier value for sample IL-02 (-170 mV), which is reduced, according to Eh-pH diagram. The following mean values were found for the parameters analyzed in this study, disregarding the outlier sample IL-02: Temperature = 26.4°C; Electrical Conductivity (EC) = 108.03 μS/cm; alkalinity = 32 mg/L; turbidity = 6.8 FTU; Total Dissolved Solids (TDS) = 62.9 mg/L; Ca2+ = 2.6 mg/L; Mg2+ = 1.04 mg/L; Na+ = 13.6 mg/L; K+ = 2.8 mg/L; Cl- = 8.2 mg/L; NO3- = 1.2 mg/L; SO42- = 1.5 mg/L. Based on the mean hydrochemical composition, the waters were classified as sodium bicarbonate. An analysis was performed to determine surfactants and tannin-lignin in the sample IL-02, resulting in values of 0.302 mg/L and 2.6 mg/L, respectively. It is believed that this sample has an excessive contribution of domestic effluents, since it has high levels of surfactants and its collection point is located close to a sewage pipe.
Keywords: Hydrochemical parameters; Oil refinery; Surface waters